Efektivitas Pelaksanaan Undang-Undang No 32 Tahun 2009 Tentang Perlindungan Dan Pengelolan Lingkungan Hidup Terhadap Tambang Emas Ilegal - Dermina Dalimunthe, Linda Sari & (Jurnal El-Thawalib, 2021)
The amount of pollution produced by the community is increasing as a result of technological advancements. The government passed Law No. 32 of 2009 on Environmental Conservation and Management. The regulations govern the disposal of B3 waste, which contains substances, energy, or other components that, directly or indirectly, pollute the environment and endanger human health. The survival of living things as a result of illegal gold mining in Hutabargot Nauli Village. There are still many violators, despite the fact that enforcement has not been effective. This is evidenced by the increasing number of offenders each year. The research question is, "How effective is the implementation of Law No. 32 of 2009 concerning environmental protection and management?" What factors contribute to the ineffectiveness of Law No. 32/2009 on environmental protection and management?. Data collection is done through interviews and documentation. The study's findings show that the enforcement of Law No. 32/2009 on Environmental Protection and Local Government Management, aided by the police and the TNI, has been carried out through raids. Uneven socialization, a lack of public awareness, economic factors, a lack of government supervision, the difficulty of obtaining an IUP, and law enforcement factors are among the issues encountered.